Ottoman empire : The genesis of the program of genocide : (1876-1920) - d; Mardanyan, Svetlana (Yerevan : Zangak-97, 2011)
[In the monograph, the process of genesis of the program og genocide in the Ottoman Empire iscomprehensively studied from the perspective of tjeoretical Genocide Studies. The book is intended for specialists and for broad circles of reading public].
Transliterations : p. 174
Bibliogr. : p. 149-174
Keywords: Armenian massacres, 1894-1896; Armenian massacres, 1909; Turkey -- Ethnic relations -- Political aspects; Armenian Genocide